Maternal fever during pregnancy and male offspring reproductive health: A longitudinal cohort study in young Danish males. (20th December 2022) - Dornfeldt, Mette Møller; Andersen, Anne‐Marie Nybo; Hougaard, Karin Sørig; Ramlau‐Hansen, Cecilia Høst; Toft, Gunnar; Bonde, Jens Peter Ellekilde; Hærvig, Katia Keglberg; Petersen, Kajsa Ugelvig; Kofoed, Ane Berger Bungum; Deen, Laura; Tøttenborg, Sandra Søgaard
Abstract: Background: Maternal fever during pregnancy has been associated with an increased risk of genital malformations, but the implication for long‐term reproductive health in the offspring is unknown. Objectives: To investigate associations between timing, duration, and temperature of fetal exposure to maternal fever and sons' semen quality, testicular volume, and levels of reproductive hormones in early adulthood. Further, to examine whether concurrent use of antipyretics and/or antibiotics modified the effect. Materials and methods: We used the Fetal Programming of Semen Quality cohort consisting of men born to women enrolled in the Danish National Birth Cohort. Self‐reported information on maternal fever was collected twice during pregnancy (median 16 and 31 pregnancy weeks) and categorized as any fever during pregnancy, fever during early pregnancy (weeks 1–15), and fever exclusively during late pregnancy (weeks 16–42). Semen quality and concentrations of reproductive hormones were measured at a clinical examination at the age of 18.9 years. We used negative binomial regression to examine the associations, adjusting for maternal age at birth, maternal smoking, family occupational status, and precision variables related to semen quality and hormonal levels, for example, abstinence time. Results: 986 men were included in the study, of which 23% had mothers reporting at least one episode of fever. We found no strong indications of associations between maternal fever during pregnancy and male reproductive health in young men. Concurrent use of antipyretics and antibiotics did not modify the association. Discussion: Strengths include the large sample size, prospectively collected data, and the adjustment for maternal factors during pregnancy and important precision variables. A limitation is the crude self‐reported information on maternal fever. Conclusion: We found no evidence to support that timing, duration, or temperature of maternal fever during pregnancy has a long‐term impact on semen characteristics, testicular volume, or level of reproductive hormones in male offspring.